X-ray Source Populations And Star-formation History In M81 - Zezas, Andreas; Gazeas, K.; Gallagher, J.; Huchra, J.; Fabbiano, G.; Nantais, J. (American Astronomical Society Meeting Abstracts, 2007)
We present the first results from a study of the X-ray source populations in M81 in the context of their local star-formation histories. We use deep Chandra observations and our multi-band HST maps of M81 in order to detect and classify the X-ray sources, based on their X-ray and optical properties. We compare the different X-ray source populations (Luminosity functions and relative numbers of different source types) for the different regions of the galaxy and for stellar populations in different age ranges (derived from the HST data). This way we can identify High-mass X-ray binaries with Main Sequence and supergiant donors, and we find that their luminosity functions are distinctly different. We also construct the luminosity functions of the X-ray sources associated with globular clusters. Finally we present our results from the spatially resolved star-formation history of M81, based on the study of the color-magnitude diagrams in different regions of the galaxy. We discuss these results in the context of similar studies of star-forming galaxies spanning a wide range of starburst ages.